Students’ Errors In Translating Thesis Abstract from Indonesian to English at English Education Program of Universitas Negeri Padang - Fitri Rutami; Witri Oktavia (Journal of English Language Teaching, 2023)
The purpose of this research is to find out the students’errors in translating abstaract from Indonesian to English at English educations program of Universitas Negeri Padang. The descriptive qualitative method was used in this research. The translation task was used as the instrument of the research.The text that was used by reasercher was thesis abstracts. The results of the study was found with the frequency of 47 times of errors. There are missing word in 11 times (23,4%), word order in 5 times (10,63%), Incorrect word in 29 times ( 61,7%), and the last was punctuation in 2 times of errors (4,25%). The Unkwown word was not found in the data.